2015
DOI: 10.1212/wnl.0000000000001807
|View full text |Cite
|
Sign up to set email alerts
|

When DLB, PD, and PSP masquerade as MSA

Abstract: Objective:To determine ways to improve diagnostic accuracy of multiple system atrophy (MSA), we assessed the diagnostic process in patients who came to autopsy with antemortem diagnosis of MSA by comparing clinical and pathologic features between those who proved to have MSA and those who did not. We focus on likely explanations for misdiagnosis.Methods:This is a retrospective review of 134 consecutive patients with an antemortem clinical diagnosis of MSA who came to autopsy with neuropathologic evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(155 citation statements)
references
References 31 publications
9
145
0
1
Order By: Relevance
“…Recent reports revealed that only 62% of patients clinically diagnosed with MSA by community neurologists have the correct diagnosis at autopsy (Koga et al, 2015). The most common diseases misdiagnosed as MSA included PD, DLB and PSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports revealed that only 62% of patients clinically diagnosed with MSA by community neurologists have the correct diagnosis at autopsy (Koga et al, 2015). The most common diseases misdiagnosed as MSA included PD, DLB and PSP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting with parkinsonism may be misdiagnosed as PD. The reverse also occurs; approximately 20% of patients with a clinical diagnosis of MSA turn out to have PD or DLB at autopsy (Koga et al, 2015). Patients presenting with the cerebellar phenotype can mimic other adult-onset ataxias due to alcohol, chemotherapeutic agents, lead, lithium, and toluene, or vitamin E deficiency, as well as paraneoplastic, autoimmune, or genetic ataxias (e.g., spinocerebellar ataxias, fragile X–associated tremor ataxia syndrome, or late-onset Friedreich ataxia) (Klockgether, 2010; Lin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This ambiguity leads to 20–40% diagnostic errors (1, 2), slow therapeutic progress (3) and suboptimal clinical outcomes. Complex neurological disorders such as multiple sclerosis (MS) are generally treated by a single disease modifying treatment (DMT), without understanding patient-specific drivers of disability.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were based on a clinical series of tertiary centers; thus, they may be not representative of the general population of parkinsonism. In fact, even the UKPDSBRC are devoted to define only PD; however, little is known about the whole spectrum of parkinsonism; a recent study investigating the accuracy of the clinical diagnosis of MSA reported a diagnostic accuracy of 62% [36]. …”
Section: Discussionmentioning
confidence: 99%